The significance of selected tests characterizing motor potential in achieving high results in speed climbing - Krawczyk, M.; Ozimek, M.; Rokowski, R.; Pociecha, M.; Draga, P. (Journal of Kinesiology and Exercise Sciences, 2019)
Study aim. The main aim of research was to verify which of the countermovement jumps (CMJ) provides the most accurate information on the possibility of obtaining the best result in a climbing run and to assess the coexistence (correlation) of the running result as well as the reaction time to an auditory signal. Material and methods. The study was conducted among a group of male climbers at the average age of 20.5 years (n=6). At the time of the measurements, the competitors presented the highest sports level and were members of the Polish National Team in the speed climbing competition. Somatic measurements were carried out successively, followed by measurements of simple reaction time and various jumps. Results. Correlations between the studied variables characteristic of somatic features as well as motor skills with climbing time were, in most cases, not significant. Statistically significant correlations at the level of p<0.05 were found between running time and the following trials: CMJb (cm) (rx,y: -0.88); PmaxCMJb (W/kg) (rx,y: -0.88) and PmaxCMJb (W/LBMkg) (rx,y: -0.86). Conclusions. CMJ without arm swing is a valuable tool in assessing the motor potential of a sprinting climber and is a test of great informative value in the context of the possibility to obtain high results in a speed climbing competition. The applied test to assess the level of response time to the auditory signal was a trial, which to a moderate extent, allows to diagnose the possibility of achieving high results in a speed climbing sprint.